Private Investment Flows in Developing Economies: Macroeconomic and Environmental Determinants - Dung, Nguyen Trung; Lan, Le Ngoc; Tinh, Bui Thi Thanh; Phuong, Nguyen Thanh (International Journal of Energy Economics and Policy, 2025)
The paper examines the macroeconomic and environmental determinants of private investment across 57 developing countries in Asia, Europe, North Africa, Sub-Saharan Africa, and Latin America during the period 2000-2023. Using the System Generalized Method of Moments (S-GMM) to address potential endogeneity and dynamic relationships, the analysis shows that rising CO2 emissions significantly reduce private investment, suggesting that environmental degradation increasingly undermines capital allocation decisions in developing economies excluding Latin America and the Caribbean. Stronger GDP growth, higher domestic credit to the private sector, and greater trade openness positively influence private investment, except in Sub-Saharan Africa and North Africa, while high inflation deters capital formation. The real exchange rate also plays a key role in shaping investor confidence, except in Sub-Saharan and North Africa. A key point in developing contexts is that stronger tax burdens do not necessarily deter private investment; instead, flows often increase, challenging traditional economic views. The results highlight the critical role of macroeconomic stability and improved environmental performance in sustaining private capital flows offering practical guidance for policymakers seeking to attract investment in an era defined by sustainability.